2015
DOI: 10.1002/sdtp.10312
|View full text |Cite
|
Sign up to set email alerts
|

11.2: Usefulness of Stereoscopic 3D Images in Elementary School Classes

Abstract: The advantages of stereoscopic 3D images in education were evaluated in an elementary schools' experimental class. The results from the worksheets filled out by students revealed that educational 3D material could help students focus on details and understand three-dimensional spaces or concavo-convex shapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This suggests that 3D images could be an effective learning tool for inducing student interest. In addition, Shibata et al reported that 3D educational materials could help students focus on specific details and understand 3D spaces or concavo-convex shapes [9].…”
Section: Effectiveness Of Stereo Viewing In Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that 3D images could be an effective learning tool for inducing student interest. In addition, Shibata et al reported that 3D educational materials could help students focus on specific details and understand 3D spaces or concavo-convex shapes [9].…”
Section: Effectiveness Of Stereo Viewing In Schoolmentioning
confidence: 99%
“…For their use in elementary school social studies classes, we considered the fact that stereoscopic 3D images are generally viewed at a different size on 3D displays and with different viewing distances in a classroom [9] by children with smaller interpupillary distances than those of adults. People who have a small interpupillary distance perforce view more emphasized stereo images than those who have a larger interpupillary distance when viewing the same stereo images on a 3D display of the same size.…”
Section: Human Factors Aspectmentioning
confidence: 99%